2013
DOI: 10.1590/s0100-69162013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the application of swine wastewater in percolate and in soil cultivated with soybean

Abstract: ABSTRACT:The aim of this study was to evaluate the possible impacts caused in the soil and in the percolate in lysimeters of drainage with application of different rates of swine wastewater (SW) during the cycle of soybean culture and to assess the productivity of it. The experiment was conducted at the Agricultural Engineering Experimental Center of UNIOESTE. The soil was classified as typical Distroferric Red Latosol. There were twenty-four drainage lysimeters in the area in which the soybean was cultivated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
(13 reference statements)
0
6
1
6
Order By: Relevance
“…The maximal concentration of K in the percolated was 59.0 kg ha -1 (ALT4), presenting a significant effect when compared to the 23.6 kg ha -1 removed in the percolate after application of the AQT0 treatment. These results were superior to those found by Brito et al (2005), in which were observed concentrations of 15.1 kg ha -1 of K in the percolation of soil columns submitted to 700 m 3 ha -1 of vinasse, and Maggi et al (2013) that observed the presence of 4.7 kg ha -1 of K in percolate of 27 lysimeters submitted to dosages of 300 m 3 ha -1 of swine wastewater (SSW).…”
Section: Resultscontrasting
confidence: 86%
“…The maximal concentration of K in the percolated was 59.0 kg ha -1 (ALT4), presenting a significant effect when compared to the 23.6 kg ha -1 removed in the percolate after application of the AQT0 treatment. These results were superior to those found by Brito et al (2005), in which were observed concentrations of 15.1 kg ha -1 of K in the percolation of soil columns submitted to 700 m 3 ha -1 of vinasse, and Maggi et al (2013) that observed the presence of 4.7 kg ha -1 of K in percolate of 27 lysimeters submitted to dosages of 300 m 3 ha -1 of swine wastewater (SSW).…”
Section: Resultscontrasting
confidence: 86%
“…Rajesh et al (2009) found an increase in soil pH (7.90 to 8.07) when applying oil-refinery effluent at various time intervals; according to the authors, this result was due to the alkaline characteristics of the effluent and the high concentrations of soluble salts. In evaluating the effect on the soil of applications of wastewater from pig farming, Cabral et al (2011) found no significant variation in pH values at the applied effluent doses; results which were confirmed by Maggi et al (2013).…”
Section: Resultsmentioning
confidence: 67%
“…MAGGI et al (2013) detectaram que os teores de K, P e N no solo aumentaram de acordo com o aumento das taxas de água residuária de suinocultura.…”
Section: Introductionunclassified